Photodynamic nasal SARS-CoV-2 decolonization shortens infectivity and influences specific T-Cell responses - Fernandez-Montero, Alejandro; Zuaznabar, Jon; Pina-Sanchez, Manuel; Maestro, Sheila; Martin-Navarro, Loreto; Muñoz-Rodríguez, Natalia; Olagüe, Cristina; Pastrana, Marta; Martínez-Fernández, Maria; Camps, Gracian; Rodriguez, Jose Antonio; Marchese, Francesco P.; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background The main objective was to evaluate the efficacy of intranasal photodynamic therapy (PDT) in SARS-CoV-2 mildly symptomatic carriers on decreasing the infectivity period. SARS-CoV-2-specific immune-stimulating effects and safety were also analysed. Methods We performed a randomized, placebo-controlled, clinical trial in a tertiary hospital (NCT05184205). Patients with a positive SARS-CoV-2 PCR in the last 48 hours were recruited and aleatorily assigned to PDT or placebo. Patients with pneumonia were excluded. Participants and investigators were masked to group assignment. The primary outcome was the reduction in in vitro infectivity of nasopharyngeal samples at days 3 and 7. Additional outcomes included safety assessment and quantification of humoral and T-cell immune-responses. Findings Patients were recruited between December 2021 and February 2022. Most were previously healthy adults vaccinated against COVID-19 and most carried Omicron variant. 38 patients were assigned to placebo and 37 to PDT. Intranasal PDT reduced infectivity at day 3 post-treatment when compared to placebo with a β-coefficient of -812.2 (CI95%= -478660 – -1.3, p<0.05) infectivity arbitrary units. The probability of becoming PCR negative (ct>34) at day 7 was higher on the PDT-group, with an OR of 0.15 (CI95%=0.04-0.58). There was a decay in anti-Spike titre and specific SARS-CoV-2 T cell immunity in the placebo group 10 and 20 weeks after infection, but not in the PDT-group. No serious adverse events were reported. Interpretation Intranasal-PDT is safe in pauci-symptomatic COVID-19 patients, it reduces SARS-CoV-2 infectivity and decelerates the decline SARS-CoV-2 specific immune-responses.